Pharmacological Management of Parkinson’s Disease: Current Therapies and Emerging Treatments - Sheilina Choudhary (International Journal of Genetic Modifications and Recombinations, 2023)
Objective: Parkinson's disease, behind Alzheimer's, is the second most common neurodegenerative ailment and a major cause of neurological morbidity worldwide. Clinical diagnosis is made, and current management is limited to symptomatic treatments, with levodopa remaining the cornerstone of pharmaceutical therapy. In certain patient groups, deep brain stimulation of specific basal ganglia targets can provide significant clinical relief. There are currently no proven disease-modifying medicines in clinical use that can halt or reverse the underlying neurodegenerative process. Methods: In this investigation, target proteins were downloaded from the PDB and docked in Biovia. The ligands' and standard medications' binding affinity with each target protein was compared and assessed. Also, only 4 substances were choosen for SWISS-ADME final results. Results: The docking result revealed that the ligands selected have the best binding affinity with all the three target proteins. Conclusion: The ligands could potentially be used to treat Parkinson’s Disease in the future approaches for studying the urge ligands in vitro and in vivo analysis in order to create novel parkinson’s inhibitors.
Keywords: Levodopa; Parkinson’s Disease; SWISS-ADMET analysis; molecular docking; phytocompounds